Anais Do XVIII Encontro Nacional De Inteligência Artificial E Computacional (ENIAC 2021) 2021
DOI: 10.5753/eniac.2021.18252
|View full text |Cite
|
Sign up to set email alerts
|

A New Heuristic for Radius Estimation in RBF Neural Networks

Abstract: Redes Neurais baseadas em Funções de Base Radial (RBFNN) são métodos clássicos do aprendizado de máquina que contêm uma camada de Funções de Base Radial (RBF) que atuam como extrator de características para a camada final, que executa o reconhecimento de padrões. A estimação do raio das RBFs é uma das atividades mais cruciais do treinamento de modelos RBFNN e afeta diretamente o seu poder de generalização e acurácia. Neste trabalho é apresentado uma nova heurística para estimação do raio e experimentos computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Ma et al [34] proposed an "a priori" articulation of preferences in MOEA/D using the weight vectors in each sub-problem. De Souza et al [16] suggested modifying the reference points in the scalarizing functions, and Li et al [30] used T-MOEA/D in an interactive framework in which the DM articulates her/his preferences through a target region given by the preferred range of objective functions. Li et al [31] proposed a Non-Uniform Mapping Scheme (NUMS) to map reference points to new positions close to the aspiration-level vector supplied by the DM.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [34] proposed an "a priori" articulation of preferences in MOEA/D using the weight vectors in each sub-problem. De Souza et al [16] suggested modifying the reference points in the scalarizing functions, and Li et al [30] used T-MOEA/D in an interactive framework in which the DM articulates her/his preferences through a target region given by the preferred range of objective functions. Li et al [31] proposed a Non-Uniform Mapping Scheme (NUMS) to map reference points to new positions close to the aspiration-level vector supplied by the DM.…”
Section: Introductionmentioning
confidence: 99%